The learning style of normal (technical) students in a neighbourhood school - Ng, Cher Fah. (2008)
The Normal (Technical) students have always 'fascinated' and at the same time 'exasperated' the educators in Singapore. Most of the Normal (Technical) students present themselves to be intelligent but learning in school seems to have escaped them. A strong suspicion is that they are capable of learning but needed a different environment from students of the other courses. The study focuses on Kolb's 'Experiential Learning Model' and 'Learning Style Inventory'. The instrument used to collect the data were three survey forms which were adapted from Kolb's (1985) Learning Style Inventory (LSI). It was found that the Normal (Technical) students favoured only the processing learning dimension (watching and doing) and almost neglected the reception learning dimension (feeling and thinking). Interestingly, the male and female students showed significant difference in their preferred learning style along the reception dimension of learning in one of the surveys. As for the three subjects of English, Mathematics and Science, these students favoured the reflective observation, the watching mode. The survey for ranking their preference in jobs and leisure and their perception of themselves did not reveal any consistent trend. The information obtained from this dissertation could provide the educators useful tips to help these special kids to begin to learn and reach a higher plateau of achievement in school.